2022
DOI: 10.7759/cureus.23636
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 Pneumonia and Genetic Susceptibility: A Case Report and Literature Review

Abstract: Genetic susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) morbidity and mortality continues to evolve. This report presents a case of an apparently healthy male adult who developed severe coronavirus disease 2019 (COVID-19) and a study on relevant genetic mutations, namely, angiotensin-converting enzyme 2 (ACE2-rs4646994 I/D) gene, glutathione S-transferase (GST) M1 and T1 gene, and miR-423 rs6505162 C>A gene polymorphism. Results showed that the ACE-DD genotype of ACE2, (GSTM1+/+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They also play an important role in idiopathic pulmonary fibrosis and lung fibro genesis [29]. Several studies have reported that SARS-CoV-2 decrease the activity of these enzymes [30]. A study in patients with COVID-19 ranging in age from 20 to 58 years showed a decrease in the GSTp1 and there was a correlation with a higher prevalence of deaths in males in comparison with female patients [31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also play an important role in idiopathic pulmonary fibrosis and lung fibro genesis [29]. Several studies have reported that SARS-CoV-2 decrease the activity of these enzymes [30]. A study in patients with COVID-19 ranging in age from 20 to 58 years showed a decrease in the GSTp1 and there was a correlation with a higher prevalence of deaths in males in comparison with female patients [31].…”
Section: Discussionmentioning
confidence: 98%
“…The temperature median was of 36 , the arterial pressure (78, 71-102 mmHg), the body temperature (36, 36.5-37.2 • C), total cholesterol (1363, 89-210 mg/dL), triglycerides (186.5, 80-726 mg/dL), high-density lipoprotein (26, 14-40 mg/dL), low-density lipoprotein (62, 40-110 mg/dL), leukocytes (8.8, 3.5-14.9 10 3 /µL), lymphocytes (8.3, 0.14-1.54 10 3 /µL), platelets median (253, 164-408 10 3 /µL), ferritin (435.4, 146-2592 ng/mL), D-dimer (605, 200-2100 µg/mL), CRP (143.15, 44.7-221 mg/L), IL-6 (16, 7.8-324 pg/mL), NR (8.4, 6-67), procalcitonin (0.23, 0.08-11.4 ng/mL). The sepsis score according to SOFA index was (0, 0-3), APACHE (5.5, 4-8), and SAPS (27,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The patients with moderate and severe condition were 8, respectively (50/50%), and the number of days with mechanic ventilation was (13,, days in ICU were (17,, and death 2 (12%).…”
Section: Demographic Characteristics Of the Patients Infected By Sars...mentioning
confidence: 99%